Investigation of wind loading characteristics of roof-mounted solar panels on tall buildings. (December 2022) - Peng, H.Y.; Song, S.S.; Liu, H.J.; Dai, S.F.; Zhang, F.L.
Abstract: Roof-mounted solar panels have become increasingly important for the development of green energy buildings. In this study, wind tunnel tests were conducted to systematically investigate the wind loading characteristics of solar panels on the square roof of a tall building. Both the isolated and 3 × 3 arrayed panels (nine zones on the roof) were studied by analyzing the mean and peak pressure/panel force coefficients. The effects of panel chord length, tilt angle, panel location, panel spacing, and parapet height were examined. Moreover, the interference effects of arrayed panels were assessed by comparison with their isolated counterparts. The most critical peak panel force coefficients occurred at the unfavorable wind directions, while the largest forces appeared at roof corners owing to the conical vortices. Hence, roof location is a crucial contributing factor for panel forces. The spacing effect exhibited different patterns at various roof zones. Arrayed panels experienced significant mutual interference effects, with an average reduction in mean wind loads of approximately 57 %. Parapets considerably reduced the negative peak loads on the isolated and arrayed panels by about 33 %–41 %. Solar panels on low-rise buildings are more susceptible to the flow reattachment than on tall buildings.